Suku Kurdi dan Potensi Konflik di Timur Tengah - Ahmad Sahide (Jurnal Hubungan Internasional, 2014)
Kurdistan tribe is the name of the ethnic unity occupying some countries in Middle East region, mainly Iraq, Iran, and Turkey. The existence of the Kurdistan tribe, with different ethnic from the majority, is always viewed as the region problem and treated discriminatively. Thus, the Kurdistan community always makes movement, even always does rebellion, for the sake of fighting their political right. This writing explains the existence and the form of the political movements of the Kurdistan, in the three main countries above, in fighting their political right, either autonomy or independence demand, even though the dreams of the Kurdistan movement is difficult to be brought into reality.